2013
DOI: 10.4300/jgme-d-12-00273.1
|View full text |Cite
|
Sign up to set email alerts
|

Reporting for Duty During Mass Casualty Events: A Survey of Factors Influencing Emergency Medicine Physicians

Abstract: Background Academic medical centers play a major role in disaster response, and residents frequently serve as key resources in these situations. Studies examining health care professionals' willingness to report for duty in mass casualty situations have varying response rates, and studies of emergency medicine (EM) residents' willingness to report for duty in disaster events and factors that affect these responses are lacking. Objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Other frequently cited barriers to willingness include fear and concern for family and personal ill-health and safety, 12,38 distance from home to the facility, 12 lack of transportation, 39 and caring for children, the elderly, or for pets. 6,7,[39][40][41] Studies have shown that a sense of duty is an influential factor in staff willingness to respond. 7,42 Two important characteristics of the respondents are noteworthy in our study.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Other frequently cited barriers to willingness include fear and concern for family and personal ill-health and safety, 12,38 distance from home to the facility, 12 lack of transportation, 39 and caring for children, the elderly, or for pets. 6,7,[39][40][41] Studies have shown that a sense of duty is an influential factor in staff willingness to respond. 7,42 Two important characteristics of the respondents are noteworthy in our study.…”
Section: Figurementioning
confidence: 99%
“…6,7,[39][40][41] Studies have shown that a sense of duty is an influential factor in staff willingness to respond. 7,42 Two important characteristics of the respondents are noteworthy in our study. First, many respondents turned to social media for information and communication during a disaster.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts between family concerns and obligations to duty have been expressed by emergency room physicians when surveyed on their willingness to respond to various disaster scenarios. 5 Similar feelings of role conflict have been described by police officers and perinatal nurses responding after hurricane Katrina in 2005. 3,11 Greater than 90% of individuals at-home indicated the storm affected their ability to go to work.…”
Section: Discussionmentioning
confidence: 61%
“…1 Research has demonstrated that the primary concerns of police officers, emergency room nurses, and physicians working as first responders during disasters, such as hurricanes, are for family safety. [2][3][4][5] Yet, no information is available assessing obstetrician-gynecologists' perceptions of role conflict during a disaster. On August 26, 2017, Hurricane Harvey made landfall on the Southeast Texas coast.…”
mentioning
confidence: 99%